Genetic causes underlying grey matter heterotopia. (November 2021) - Vriend, Ilona; Oegema, Renske
Abstract: Grey matter heterotopia (GMH) can cause of seizures and are associated with a wide range of neurodevelopmental disorders and syndromes. They are caused by a failure of neuronal migration during fetal development, leading to clusters of neurons that have not reached their final destination in the cerebral cortex. We have performed an extensive literature search in Pubmed, OMIM, and Google scholar and provide an overview of known genetic associations with periventricular nodular heterotopia (PNVH), subcortical band heterotopia (SBH) and other subcortical heterotopia (SUBH). We classified the heterotopias as PVNH, SBH, SUBH or other and collected the genetic information, frequency, imaging features and salient features in tables for every subtype of heterotopia. This resulted in 105 PVNH, 16 SBH and 25 SUBH gene/locus associations, making a total of 146 genes and chromosomal loci. Our study emphasizes the extreme genetic heterogeneity underlying GMH. It will aid the clinician in establishing an differential diagnosis and eventually a molecular diagnosis in GMH patients. A diagnosis enables proper counseling of prognosis and recurrence risks, and enables individualized patient management.